Antioxidant activity of hyaluronic acid investigated by means of chemiluminescence of equine neutrophil bursts and electron paramagnetic resonance spectroscopy. Issue 1 (28th July 2014) - Braga, P. C.; Dal Sasso, M.; Lattuada, N.; Greco, V.; Sibilia, V.; Zucca, E.; Stucchi, L.; Ferro, E.; Ferrucci, F.
<x xml:space="preserve">Abstract</x> Activated neutrophils (PMNs), the ROS/RNS released by PMNs and the derived inflammatory processes are involved in the pathogenesis and progression of human inflammatory airway diseases. Similar diseases are also present in horses which suffer from recurrent airway obstruction (RAO), exercise‐induced pulmonary haemorrhage (EIPH) and inflammatory airway diseases (IAD). Hyaluronic acid (HA) plays numerous roles in modulating inflammatory processes. The aim of this study was to examine whether a preparation of HA (MW 900 000 Da) interferes with ROS/RNS during the course of equine PMN respiratory bursts, and to establish the lowest concentration at which it still has antioxidant activity by means of luminol‐amplified chemiluminescence (LACL). Electron paramagnetic resonance (EPR) spectroscopy was also used to investigate the direct antiradical activity of HA. The hydroxyl radical was significantly scavenged in a concentration‐dependent manner at HA concentrations ranging from 2.5 to 0.16 mg/mL. Superoxide anion, Tempol radical and the ABTS+were significantly inhibited at concentrations ranging from 2.5 to 0.62 mg/mL. The LACL of stimulated equine neutrophils showed that HA induced a statistically significant concentration–effect reduction from 5 mg/mL to 1.25 mg/mL. These findings were confirmed also when l‐Arg was added to investigate the inhibition of the resulting peroxynitrite anion. Our findings indicate that, in addition to the human use, HA can also be used to antagonize the oxidative stress generated by free radicals in horses peripheral blood mononuclear cells (PBMCs). In order to achieve therapeutic concentrations, a direct aerosol administration to horses with horse respiratory diseases can be considered, as this route of application is also recommended in human medicine.